Perancangan Antena Array Ultra Wideband Menggunakan Metode Defected Ground Structure (DGS) Berbentuk Bee Comb Untuk Pendeteksian Tumor Pada Otak - Fadhli Kabir; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Cancer and brain tumors are very serious diseases and problems for human health. Early detection of brain tumors is indispensable considering that every year the victims are increasing. Ultra Wideband microwave imaging is a technique that uses electromagnetic signals with wide bandwidth to see through the internal structure of the brain. This study introduces a circular and rectangular array antenna design in a circle configuration that operates in frequency range from 2 GHz to 13 GHz, the antennas are designed and simulated to detect the presence of tumors. The analysis was carried out by comparing E-Field, H-Field, the number of Specific Absorption Rate (SAR) with tumors. With a circle configuration, each antenna element faces directly into brain phantom for better tumor detection. From the simulation results, E-Field and H-Field are obtained in the brain with tumors. The SAR obtained is around 29.7 W / Kg.Keywords: Brain Cancer, Ultra Wideband (UWB), Microwave Imaging, Specific Absorption Rate (SAR), Array Antenna.